PPARδ activation in human myotubes increases mitochondrial fatty acid oxidative capacity and reduces glucose utilization by a switch in substrate preference. (February 2014) - Feng, Yuan Z.; Nikolić, Nataša; Bakke, Siril S.; Boekschoten, Mark V.; Kersten, Sander; Kase, Eili T.; Rustan, Arild C.; Thoresen, G. Hege
Abstract The role of peroxisome proliferator-activated receptor δ (PPARδ) activation on global gene expression and mitochondrial fuel utilization were investigated in human myotubes. Only 21 genes were up-regulated and 3 genes were down-regulated after activation by the PPARδ agonist GW501516. Pathway analysis showed up-regulated mitochondrial fatty acid oxidation, TCA cycle and cholesterol biosynthesis. GW501516 increased oleic acid oxidation and mitochondrial oxidative capacity by 2-fold. Glucose uptake and oxidation were reduced, but total substrate oxidation was not affected, indicating a fuel switch from glucose to fatty acid. Cholesterol biosynthesis was increased, but lipid biosynthesis and mitochondrial content were not affected. This study confirmed that the principal effect of PPARδ activation was to increase mitochondrial fatty acid oxidative capacity. Our results further suggest that PPARδ activation reduced glucose utilization through a switch in mitochondrial substrate preference by up-regulating pyruvate dehydrogenase kinase isozyme 4 and genes involved in lipid metabolism and fatty acid oxidation.